A Development of a Research-Based Project Learning Model to Cultivate an Entrepreneurial Spirit in Entrepreneurship Subjects At Pagaralam Muhammadiyah High School - syahrizal rosena; Leny Noviani; Feri Setyowibowo (Yayasan Azhar Amanaa Yogyakarta, 2024)
This research aims to: 1) Develop a research-based project learning model in entrepreneurship subjects that can foster the entrepreneurial spirit of students at SMK Muhammadiyah Pagaralam. 2) To determine the effectiveness of the Research Based project learning model in entrepreneurship subjects which can foster the entrepreneurial spirit of students at SMK Muhammadiyah Pagaralam. The research approach used is Research and Development (RnD). The product developed is a learning module that has gone through a validation process by experts and was tested in one class. The results of this trial are the basis for revising the learning module product to produce a final product that can be used. The revised product was then validated by 3 experts and tested in two classes. The effectiveness test was carried out using paired sample test analysis. The implementation of the Research-Based PjBL Model in Entrepreneurship subjects at Muhammadiyah Pagaralam Vocational School has had a positive and effective impact. The findings show a positive impact on students' motivation and skills, as well as a contribution to increasing entrepreneurial spirit. The learning modules developed have been validated and have a significant impact on learning. However, the evaluation highlights aspects that need improvement, such as the level of difficulty of the material, learning resources and learning activities. This becomes the basis for continuous improvement in improving the quality of learning.